2020
DOI: 10.1021/acsnano.0c04702
|View full text |Cite
|
Sign up to set email alerts
|

Strong Electron–Phonon Interaction in 2D Vertical Homovalent III–V Singularities

Abstract: Highly polar materials are usually preferred over weakly polar ones to study strong electron-phonon interactions and its fascinating properties. Here, we report on the achievement of simultaneous confinement of charge carriers and phonons at the vicinity of a 2D vertical homovalent singularity (antiphase boundary, (APB)) in an (In, Ga)P/SiGe/Si sample. The impact of the electron-phonon interaction on the photoluminescence processes is then clarified, by combining transmission electron microscopy, X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
1
12
0
1
Order By: Relevance
“…While some APBs follow the [110] or [−110] directions (blue lines), and are thus expected to follow the 𝜎°charge configuration, numerous other APBs are lying along other directions (red lines), and are thus expected to follow the 𝜎 +/− charge configuration or intermediate ones. This is in good agreement with the atomically-resolved observations performed in previous works [19,21] and is not fully surprising as the APBs naturally result from the coalescence of monodomain islands. [16] The simplified picture given here does not take into account the possible charge compensation effects which could occur during the growth.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…While some APBs follow the [110] or [−110] directions (blue lines), and are thus expected to follow the 𝜎°charge configuration, numerous other APBs are lying along other directions (red lines), and are thus expected to follow the 𝜎 +/− charge configuration or intermediate ones. This is in good agreement with the atomically-resolved observations performed in previous works [19,21] and is not fully surprising as the APBs naturally result from the coalescence of monodomain islands. [16] The simplified picture given here does not take into account the possible charge compensation effects which could occur during the growth.…”
Section: Resultssupporting
confidence: 93%
“…Beyond materials developments, physical properties of the specific stoichiometric APBs (with equal numbers of III–III and V–V bonds within the same APB) were recently clarified. [ 21 ] It was demonstrated that the electronic bandgap is reduced by 2D electronic localization, and that, an intrinsic and strong electron‐phonon coupling arises in stoichiometric APBs and impacts the photoluminescence properties. [ 21 ] Therefore, APBs should no longer be considered as usual non‐radiative recombination centers, but as a 2D homovalent singularities with specific symmetry properties in a bulk semiconducting matrix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These so-called anti-phase boundaries (APBs) consist of III-III and/or V-V bonds, [23,24] resulting locally in an excess or a lack of charges, and in a significant modification of the electronic band structure and vibrational properties. [25,26] Threading APBs are therefore a critical issue as far as they introduce efficient vertical electrical path within the III-V heterostructure, thereby killing the performances of any p-n junction device. [25,27] Engineering the APBs generation and propagation at the early stages of the III-V growth on Si is thus the only way to fully benefit from the ultimate properties of integrated III-V semiconductors and a major prerequisite for the successful monolithic integration of III-V optoelectronic devices on Si photonic platforms [28,29] or III-V/Si energy harvesting devices.…”
Section: Introductionmentioning
confidence: 99%